Global patterns and trends in heart failure burden under chronic respiratory disease cause categories among adults aged 55 years and older: A systematic analysis based on the GBD 2021 Study - Yinqin Liu; Anran Xu; Chen Zhang; ZhenYi Li; Shaobin Li; Hong Fang (PLoS ONE, 2026)
Background Chronic respiratory diseases (CRDs) and heart failure (HF) impose substantial global burdens. However, the long-term population-level burden of HF impairment under CRD cause categories remains insufficiently characterized within the GBD framework. Methods Using GBD 2021 data, we estimated the prevalence and years lived with disability (YLDs) of HF impairment under CRD cause categories among adults aged ≥55 years from 1990 to 2021. CRD cause categories included chronic obstructive pulmonary disease (COPD), interstitial lung disease and pulmonary sarcoidosis (ILD&PS), and pneumoconiosis (PC). Cases, rates, relative changes, and EAPCs were used as primary descriptive measures. Joinpoint regression, age–period–cohort analysis, inequality indices, and BAPC-based projections were used as secondary analyses to describe trend timing, age–cohort patterns, socioeconomic distribution, and historical-trend extensions through 2032. Results From 1990 to 2021, the global prevalent cases and YLDs of HF impairment under CRD cause categories increased markedly, while prevalence and YLD rates changed only modestly overall. The burden rose sharply with age, especially after age 75, and was generally higher in males. Temporal trends differed across periods. Patterns varied across SDI strata and differed by CRD subtype. Model-based extensions of historical patterns suggested that this burden pattern may remain substantial through 2032. Conclusion The burden of HF impairment under CRD cause categories showed marked population-level variation across age, sex, SDI strata, and CRD subtypes. These findings may help inform burden monitoring, public health planning, resource allocation, and long-term service planning for older adults.